A preliminary study of the multilingual dictionary Gujin Shilin (Kokeum Seklim) of the Joseon Dynasty: Its compilation background, structure, content and value. (June 2019) - Lee, Kyeongwon; Yurn, Gyudong; Lee, Sujin; Kim, Taewoo
Gujin Shilin 古今释林 is a multilingual dictionary, published in 1789 by Yi Ui-Pong (李义凤). The initial motivation for publishing the book was to supplement the incompleteness of other commentary books on Zhuzi Yulei 朱子语类, including Yi Hwang's (李滉) Yulujie 语录解. At last, Yi Ui-Pong completed his project as an unabridged encyclopedia of East Asian languages based on more than 1500 Jingshiziji 经史子集 (classics, history, philosophy and collections of belle letters) of China and Korea. The book has been understudied because of its enormous number of entries, its inaccessibility due to the many languages used within, and its lack of readability due to typos and variant letters. Therefore, the goal of the present paper is to analyze the background of the publication of Gujin Shilin, and its structure, content and research value. Gujin Shilin contains vocabulary from Mongolian, Manchu, Japanese, Vietnamese, Thai as well as Korean and Chinese from different historical periods. These can be used as invaluable data for the study of international studies involved in each field, including the phonological changes that the Asian languages have gone through, the interrelation among Asian languages and their mutual influences, the linguistic life, culture and custom shared by the 'Chinese character cultural sphere' countries and the study of the variant Chinese characters.